The Concept of Giving Punishment Perspective Ibnu Sahnun and Its Application to the Islamic Education System in Indonesia - Umam, Muhammad Rafli; Inayati, Nurul Latifatul (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This research is a qualitative research aimed at describing the concept of punishment by Ibnu Sahnun and its application in the Islamic education system in Indonesia. This research is motivated by Ibnu Sahnun's ideology, which states that the purpose of education is the formation of ethics in general, and this idea aligns with the prevailing regulations in Indonesia. Considering the low quality of moral education in Indonesia, the application of Ibnu Sahnun's concept of punishment can enhance the morality of students while still focusing on its educational significance. Ibnu Sahnun's method of punishment is closely tied to the Islamic education system as it is based on the Quran and Sunnah, aiming to nurture God-fearing individuals and develop dynamic human beings for both worldly and hereafter well-being. This approach also aligns with Indonesia's regulations on punishment, emphasizing that teachers should not use punishment solely for "deterrence." The primary concern should be the internal or personal issues of the child/student. The punishment received by a child should motivate them to avoid repeating mistakes and to always follow school rules. The results of this research indicate that the implementation of Ibnu Sahnun's ideas in the Indonesian education system can: 1) promote diversity among individuals who understand egalitarianism (equality); 2) disseminate religious knowledge through education; 3) generate knowledge and attain maghfirah as a means of achieving the intended goals; 4) achieve worldly life; 5) seek sustenance; and 6) uphold noble morals.